Classificação etnopedológica dos solos e relação com a capacidade de uso das terras agrícolas no município de Campina do Monte Alegre - SP - Fernandes, Amanda Augusta (Universidade Federal de São Carlos, 2020)
Integrating empirical and scientific knowledge on the soil enables the construction of a more comprehensive thought, since both local and scientific knowledge are complementary. Thus, this research aimed to identify and qualify the empirical knowledge of farmers in the municipality of Campina do Monte Alegre-SP on the classification and agricultural use of soils and to relate it to the Brazilian Soil Classification System and to the classification of land use capacity. In order to carry out the ethnopedological research, 20 agricultural areas were sampled and 17 farmers interviewed. The methodology consisted of the following steps: 1) preparation of the semi-structured script and conducting the interviews; 2) sampling and morphological description of the soils; 3) systematization and content analysis of the interviews; 4) elaboration of maps. It was found that the main ethnopedological attributes used by farmers were color, texture, consistency, fertility, acidity, organic matter and indicator plants. For the formal classification, the Brazilian Soils Classification System was used as a reference. Five ethnopedological classes and their respective soil classes were raised “Terra Vermelha or Campo” (Ferralsols and Lixisols); “Terra Roxa” (Nitisols); “Terra Branca” (Plinthsols and Gleysols); “Terra de Areia” (Lixisols, Acrisols or Alisols) and the ethnopedological class “Terra de Cultura” (Chernozems). The ethnopedological classes “Terra Vermelha or Campo” and “Terra Roxa” prodominated in the agricultural areas visited, they were classified by classes and subclasses II e,s and III e,s of land use capacity, according to the manual for utility surveying and land classification in the use capacity system.
Ethnopedological classification of soils and relationship with capacity to use agricultural land in the municipality of Campina de Monte Alegre - SP
Keywords: Etnopedologia; Sistema brasileiro de classificação do solo; Classificação de terras agrícolas; Ethnopedology; Brazilian soil classification system; Agricultural land classification; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::GENESE, MORFOLOGIA E CLASSIFICACAO DOS SOLOS